The Family Firm Monarchy, Mass Media and the British Public, 1932-53 - Owens, Edward (New Historical Perspectives, 2019)
The Family Firm presents the first major historical analysis of the transformation of the royal household's public relations strategy in the period 1932-1953. Beginning with King George V's first Christmas broadcast, Buckingham Palace worked with the Church of England and the media to initiate a new phase in the House of Windsor's approach to publicity. This book also focuses on audience reception by exploring how British readers, listeners, and viewers made sense of royalty's new media image. It argues that the monarchy's deliberate elevation of a more informal and vulnerable family-centred image strengthened the emotional connections that members of the public forged with the royals, and that the tightening of these bonds had a unifying effect on national life in the unstable years during and either side of the Second World War. Crucially, The Family Firm also contends that the royal household's media strategy after 1936 helped to restore public confidence in a Crown that was severely shaken by the abdication of King Edward VIII.